Unlocking the passivation nature of the cathode–air interfacial reactions in lithium ion batteries - Lianfeng Zou (Nature Portfolio, 2020)
Environmentally triggered degradation at the cathode–air interface is dictated by Li-ion de-intercalation caused by Li+-water interactions. Here, thin disordered rocksalt surface layers are reported to suppress chemical delithiation, facilitating development of high energy and stability cathodes.